Students group formation for an English conversation class using 0-1 integer linear programming - Engku Abu Bakar, Engku Muhammad Nazri; Hashim, Zakiah; Bidin, Siti Jamilah (Akademia Baru, 2018)
In this paper, we illustrate the application of 0-1 integer linear programming to form a small discussion group among students of an English conversation class at Universiti Utara Malaysia. The model was developed to ensure that each group consists of not more than four students, the probability for each group to be actively engaged in conversation activities is high, each group consists of a mix of gender and race composition, as well as some other specific requirements set by the instructor of the class. The optimal solution was obtained with the help of Lingo 11. The same approach can be extended to solve some other classroom management problems.